Comparative Assessment of Nicotine Content, Toxicity Level, and IC50 Values in Nicotine Products: Public Health Implications - Amna Yousaf; Anum Hayat; Urooj Fatima; Laiba Naseem; Zukhraf Usma; Rahila Huma; Rubina Munir (Journal of Toxicology)
Nicotine is highly addictive and is available in various products. The rising popularity of trendy alternative nicotine products has raised concerns about their addictive potential and toxicity, highlighting the need for comprehensive analysis and proper labeling. Current study analyzed the nicotine content in different products, revealing that e-cigarettes contained the highest concentration of nicotine, while tea and coffee had the lowest. Alarmingly, 56% of the samples were found to be poisonous, 16% were toxic, and 28% fell into the mild toxicity category for a 70 kg body weight. Additionally, many nicotine products often mislabel their nicotine content and provide inaccurate information. Multivariate statistical analysis methods, such as ANOVA, confirmed the significance of these findings. The Welch and Brown–Forsythe values of 0.026 and 0.011, respectively, indicate that the mean values of the samples were statistically significant. Further evaluation of cigarette brands included assessing total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity. Among the cigarette brands, Marlboro had the highest IC50 value at 658.8, while Milano had the lowest IC50 value at 385.9. Most brands also exhibited toxic heavy metal content, which may lead to serious health implications.